2016
DOI: 10.1080/0886022x.2016.1257433
|View full text |Cite
|
Sign up to set email alerts
|

H2S improves renal fibrosis in STZ-induced diabetic rats by ameliorating TGF-β1 expression

Abstract: Nephropathy develops in many patients with type 1 diabetes mellitus (T1DM). However, the specific mechanisms and therapies remain unclear. For this purpose we investigated the effects of hydrogen sulfide (H2S) on renal fibrosis in streptozotocin (STZ) induced diabetic rats and its underlying mechanisms.Experimental rats were randomly divided into four groups: Control group (normal rats), DM group (diabetes rats), DM + NaHS group [diabetes rats treated with sodium hydrosulfide (NaHS)], and NaHS group (normal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
(30 reference statements)
2
22
0
Order By: Relevance
“…The type 2 DM rat model was established as previously described [27,28]. Briefly, Sprague-Dawley rats (190-210 g) were randomly divided into four groups: control group (n = 12), T2D group (n = 12), T2D + PBS group (n = 12), and T2D + Cur group (n = 12).…”
Section: Type 2 Diabetes Mellitus Induction and Treatmentmentioning
confidence: 99%
“…The type 2 DM rat model was established as previously described [27,28]. Briefly, Sprague-Dawley rats (190-210 g) were randomly divided into four groups: control group (n = 12), T2D group (n = 12), T2D + PBS group (n = 12), and T2D + Cur group (n = 12).…”
Section: Type 2 Diabetes Mellitus Induction and Treatmentmentioning
confidence: 99%
“…Recent studies have revealed the existence of a close relationship between MMP-7 and TGF-β signaling (Figure 2 ). Li et al ( 2017 ) observed that the expression of TGF-β1 and MMP-7 are upregulated in STZ-induced diabetic nephropathy rats but markedly decreased in diabetic nephropathy rats treated with sodium hydrosulfide (Li et al, 2017 ), which suggests regulation between TGF-β and MMP-7. MMP-7 is also closely related to TGF-β/Smad4 signaling (Xiao et al, 2016 ).…”
Section: Biological Characteristics Of Mmp-7mentioning
confidence: 99%
“…The results of this study showed that MMP-1, MMP-2, MMP-9, and MMP-14 were significantly increased in mice in the contusion group, while the H 2 S treatment group had decreased mRNA levels of MMPs (MMP-1, MMP-2, MMP-9, and MMP-14) compared with the contusion group (Figure 7). In models of diabetes-induced kidney injury (Li et al, 2017) and myocardial fibrosis (Xiao et al, 2015), H 2 S reduced kidney injury and myocardial fibrosis by lowering the levels of MMPs. In addition, MMPs are significantly up-regulated in the dystrophic muscle of mdx mice, and the absence or inhibition of MMPs can significantly improve muscle structure and function, and reduce muscle fibrous necrosis in MDX mice (Kumar et al, 2010;Hindi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%